Profil Penggunaan Obat Kombinasi Risperidone-Clozapine dan Risperidone dengan Antipsikotik Lain pada Pasien Gangguan Mental Psikotik di Rumah Sakit Jiwa Grhasia Yogyakarta - Mexsi Mutia Rissa; Endang Darmawan; Arum Siwinarni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Approximately 7% of Indonesia's population experience mental disorders psychosis. Yogyakarta Special Region is the second-highest incidence of psychotic mental disorders with a rate of 10 per 1000 population and 80% of those treated in mental hospitals with schizophrenia. Pharmacotherapy management in patients with psychotic mental disorders with the use of antipsychotics, both single and combination. Antipsychotics are classified as atypical antipsychotics and typical antipsychotics. Both groups of antipsychotics have the same pharmacological activity, namely blocking dopamine D2 receptors. The study design is prospective. Inclusion criteria for adult patients (18-65 years), who are inpatient, get risperidone-clozapine antipsychotic therapy and risperidone with other antipsychotics and have complete data. Data obtained from medical records and analyzed with univariate tests to describe the distribution of patients. Bivariate testing to compare the two treatment groups. The number of samples at the end of the study were 32 patients who were divided into 2 groups of antipsychotic antipsychotics, risperidone-clozapine, and risperidone with other antipsychotics. The results of this study show that the therapeutic group that is often used is the combination of risperidone-clozapine compared to risperidone with other antipsychotics in patients with psychotic mental disorders at Yogyakarta Grhasia Mental Hospital.